A Modified Coupled Spectrophotometric Method to Detect 2-5 Oligoadenylate Synthetase Activity in Prostate Cell Lines. Issue 1 (December 2016) - Bhosle, Sushma; Hunt, Aisha; Chaudhary, Jaideep
Abstract Background 2'-5' oligoadenylate synthetases (OAS) are interferon inducible enzymes that polymerizes ATP to 2'-5'-linked oligomers of adenylate (2-5As). As part of the innate immune response, these enzymes are activated by viral double stranded RNA or mRNAs with significant double stranded structure. The 2-5As in turn activate RNaseL that degrade single stranded RNAs. Three distinct forms of OAS exist in human cells (OAS1, 2 and 3) with each form having multiple spliced variants. The OAS enzymes and their spliced variants have different enzyme activities. OAS enzymes also play a significant role in regulating multiple cellular processes such as proliferation and apoptosis. Moreover, Single nucleotide polymorphisms that alter OAS activity are also associated with viral infection, diabetes and cancer. Thus detection of OAS enzyme activity with a simple spectrophotometric method in cells will be important in clinical research. Results Here we propose a modified coupled spectrophotometric assay to detect 2-5 oligoadenylate synthetase (OAS) enzyme activity in prostate cell lines as a model system. The OAS enzyme from prostate cancer cell lysates was purified using Polyinosinic: polycytidylic acid (poly I:C) bound activated sepharose beads. The activated OAS enzyme eluted from Sepharose beads showed expression of p46 isoform of OAS1, generally considered the most abundant OAS isoform in elutes from DU14 cell line but not in other prostate cell line. In this assay the phosphates generated by the OAS enzymatic reaction is coupled with conversion of the substrate 2-amino-6-mercapto-7-methylpurine ribonucleoside (methylthioguanosine, a guanosine analogue; MESG) to a purine base product, 2-amino-6-mercapto-7-methylpurine and ribose1-phosphate via a catalyst purine nucleoside phosphorylase (phosphorylase) using a commercially available pyrophosphate kit. The absorbance of the purine base product is measured at 360 nm. The higher levels of phosphates detected in DU145 cell line indicates more activity of OAS in this prostate cancer cell line. Conclusion The modified simple method detected OAS enzyme activity with sensitivity and specificity, which could help in detection of OAS enzymes avoiding the laborious and radioactive methods.